Gut microbiome diversity of porcine peritonitis model of sepsis - Chalupova, Miroslava; Horak, Jan; Kramna, Lenka; Nalos, Lukas; Stengl, Milan; Chudejova, Katerina; Kraftova, Lucie; Cinek, Ondrej; Klein, Pavel; Matejovic, Martin; Hrabak, Jaroslav (Scientific reports, 2022)
Animal models are essential in understanding of the mechanisms of sepsis moreover the development and the assessment of emerging therapies. In clinically relevant porcine model, however, a significant variability in the host response has been observed among animals. Thus, there is a strong demand to better understand the potential sources of this heterogeneity. In this study, we compared faecal microbiome composition of 12 animals. Three samples were collected at different time points from each animal. Bacteriome was subjected to 16S rDNA profiling. A significant difference in bacterial composition was associated with the season (p < 0.001) but not with the sex of the pig (p = 0.28), the timing of sample collection (p = 0.59), or interactions thereof (all p > 0.3). The season batch explained 55% of the total variance in the bacteriome diversity. The season term was highly significant from the high-resolution level of the bacterial amplicon sequencing variants up to the level of phylum. The diversity of the microbiome composition could significantly influence experimental model of sepsis, and studies are warranted to demonstrate the effects of gut microbiome diversity on the host-response. If confirmed, control of the gut microbiome should become a standard part of the pre-clinical sepsis experiments.
Keywords: Swine; prasata; RNA, Ribosomal, 16S; RNA ribozomální 16S; Sepsis; zvířata; střevní mikroflóra; DNA, Ribosomal; peritonitida; Bacteria; Gastrointestinal Microbiome; ribozomální DNA; Peritonitis; sepse; Animals